Molecular mechanisms and epidemiology of fosfomycin resistance in enterococci isolated from patients at a teaching hospital in China, 2013–2016. (March 2020) - Zhang, Xiucai; Bi, Wenzi; Chen, Lijiang; Zhang, Yizhi; Fang, Renchi; Cao, Jianming; Zhou, Tieli
Highlights: Fosfomycin possess strong bacteriostatic activity against enterococci. Low fosfomycin resistance rate of 2.6% (20/761). Presence of fosB gene, amino acid mutations in MurA, and high expression level of fosX were the main resistance mechanisms. Clonal spread of ST78 fosfomycin-resistant enterococci and other sporadic STs in a single hospital. Abstract: Objectives: The aim of this study was to investigate the mechanisms of fosfomycin resistance and epidemiological characteristics in fosfomycin-resistant enterococci in China. Methods: A collection of 761 enterococcal clinical isolates from a teaching hospital in Wenzhou, China were studied. The fosfomycin susceptibility of the isolates was investigated by the agar dilution method. The isolates were also analysed for mechanisms of re fosfomycin resistance by PCR and quantitative real-time PCR. Furthermore, pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) were performed to analyse the molecular epidemiological characteristics of the fosfomycin-resistant isolates. Results: In this study, 0.3% (1/372) of Enterococcus faecalis and 4.9% (19/389) of Enterococcus faecium clinical isolates were found to be resistant to fosfomycin. Among the 20 fosfomycin-resistant isolates, 5 harboured the fosB gene, 10 carried multiple amino acid substitutions in MurA, and 6 showed high-level expression of the fosX gene; of note, 1 isolate simultaneously carried fosB and amino acid mutation in MurA. Furthermore, a high degree of homology in the fosfomycin-resistant enterococci was confirmed using MLST and PFGE. Conclusion: These finding demonstrate that the fosB gene, mutations in the fosfomycin target enzyme MurA, and a high expression level of fosX were the resistance mechanisms in these fosfomycin-resistant enterococci.